Digital Heterotopias in the Metaverse: The (g)Ender Gallery by Cat Haines (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
At a time when the umbrella term “metaverse” seems to have monopolised the discourse on online social presence, this paper aims to explore the possibility of constructing interactive online spaces that challenge the hegemonic structures of heteronormative society. Before describing the metaverse as a futuristic scenario that catalyses technophobic fears, perhaps we can turn our attention to existing metaverses: one example is the sandbox video game Minecraft, which is characterised by great interactivity and manipulability. Therefore, by analysing the immersive and interactive artwork g(Ender Gallery) by artist Cat Haines, which was created entirely on Minecraft in 2021, I will explore how the platform can be used to build a playful ground and at the same time a critical arena of gender norms and a deep reflection on trans experience.
Keywords: Metaverse; Minecraft; Gender studies; Feminist; Feminist art history